Pemetaan Risiko Hepatitis A dengan Sistem Informasi Geografis (SIG) di Kabupaten Jember Tahun 2013 (The Mapping of Hepatitis A Risk with Geographic Information System (GIS) in Jember District, 2013) - Adinda Intan Putri Pertiwi; Andrei Ramani; Yunus Ariyanto (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Hepatitis A is an inflammation of the liver disease caused by Hepatitis A virus. Jember was an area that often became endemic of Hepatitis A. The aim of this study was to describe the spread of Hepatitis A and the spreading pattern of the risk of hepatitis A in 2013 by using a Geographic Information System (GIS). This type of research uses descriptive method. Risk factor of Hepatitis A studied clean live and healthy behavior, defecation behavior, clean water access, family privy, waste management, number of street food corner, and population density. There are two types of maps that will be produced Hepatitis A case maps and Hepatitis A risk factor maps. The technique of data analysis used grading, scoring and calculation of the strength of the infection. The risk level is divided into three classes, namely high (score 1), moderate (score 2) and low (score 3). The results showed that there were 183 cases of Hepatitis A were recorded from medical records of RSD dr. Soebandi, RSD Balung, RS Bina Sehat and RS Jember Klinik in 2013, 27% (51 people) are in the age range 21-30 years, whereas 115 male sex. Areas that have cases with high category Sumbersari and Patrang subdistrict. An area that has Hepatitis A infection strength with high category Silo and Kaliwates subdistrict. The difference Hepatitis A case maps and Hepatitis A risk factor maps becaused low hygiene of food handle and inexact food management. Keywords: risk, case, Geographic Information System, force of infection